2012
DOI: 10.1007/s11999-012-2515-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Femoral Component Rotation in a TKA Reliably Guided by the Functional Flexion Axis?

Abstract: Background The position of the femoral component in a TKA in the axial plane influences patellar tracking and flexion gap symmetry. Errors in femoral component rotation have been implicated in the need for early revision surgery. Methods of guiding femoral component rotation at the time of implantation typically are derived from the mean position of the flexion-extension axis across experimental subjects. The functional flexion axis (FFA) of the knee is kinematically derived and therefore a patient-specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…To maintain an even gap at 90° or higher flexion using s-TEA may need to consider the condyle height differences of the medial and lateral condyles. Recently, the GCA has been suggested as a reproducible and reliable reference to optimize femoral component positioning during TKA (Colle et al, 2012; Doro et al, 2008; Howell et al, 2013; Matziolis et al, 2011; Oussedik et al, 2012), since it is believed that the alignment of TKA with GCA could replicate normal knee kinematics, such as medial pivot motion, and could produce an appropriate ligament balance after TKA (Blaha, 2004; Blaha et al, 2003). The different height of the GCA at full extension and 90° of flexion may need to be considered for gap balance at the two position of the knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain an even gap at 90° or higher flexion using s-TEA may need to consider the condyle height differences of the medial and lateral condyles. Recently, the GCA has been suggested as a reproducible and reliable reference to optimize femoral component positioning during TKA (Colle et al, 2012; Doro et al, 2008; Howell et al, 2013; Matziolis et al, 2011; Oussedik et al, 2012), since it is believed that the alignment of TKA with GCA could replicate normal knee kinematics, such as medial pivot motion, and could produce an appropriate ligament balance after TKA (Blaha, 2004; Blaha et al, 2003). The different height of the GCA at full extension and 90° of flexion may need to be considered for gap balance at the two position of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…The transepicondylar axis (TEA) and the geometrical center axis (GCA) are widely used in knee joint kinematics analysis (Asano et al, 2001; Berger et al, 1993; Eckhoff et al, 2007; Li et al, 2013; Matsuda et al, 2003; Most et al, 2004; Oussedik et al, 2012; Victor et al, 2009). A TEA could be referred to the clinical TEA (c-TEA) or surgical TEA (s-TEA) based on the different bony landmarks used to define the axes on the medial femoral epicondyle (Berger et al, 1993; Griffin et al, 2000; Victor et al, 2009; Yoshino et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the rotational alignment of the femoral component not only affects tracking of the patellar component but also determines the flexion gap of the femoral component [ 2 , 13 ]. Previous studies suggested using the posterior condylar axis (PCA) [ 12 ], Whiteside’s line [ 18 ] or the transepicondylar axis (TEA) [ 9 , 11 , 14 , 20 ] as a reference axis for determining rotational alignment of the femoral component, and there have been studies on the angles created between these reference axes [ 8 , 12 , 15 , 16 , 18 ]. However, it is not always easy to apply such traditional references in the operative field because arthritic changes such as deformities, bony defects and osteophytes not only make it difficult to identify these references but also distort them [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on anatomical and kinematic data, the accepted gold standard for correct femoral component rotation is the SEA measured on a CT scan [ 2 , 4 , 11 , 28 , 30 ]. Unfortunately, both epicondyles are relatively broad structures covered in dense soft tissue in vivo making them difficult to identify intraoperatively [ 3 , 22 , 39 ].…”
Section: Introductionmentioning
confidence: 99%